CHARACTER EDUCATION INTEGRATION IN SOCIAL STUDIES LEARNING - Agung, Leo (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2011)
Recently many violent and moral degradations occurred in Indonesia have affected most of the youth. The moral degradation symptoms are indicated by the increase of drug abuse, free sex, crime, violent act, and many other disrespectful behaviors. The source of this multidimensional crisis and the nation’s downturn is the identity crisis and the failure in developing the nation’s character education. The IPS (the social studies) lesson is, in fact, aimed at improving the personal, social, and intellectual competences. Therefore, it is the time to integrate the character education with the school’s lessons, particularly in the social studies or IPS in the level of junior high school. In this case, the lesson is expected to be a tool and opportunity for students to develop various good characteristics such as religious, honest, integrited, tolerant, discipline, independent, hard worker, creative, patriotic, and friendly qualities.